Implementation of the CTL Model to Increase Student Activity and Learning Outcomes in Class IV IPS Learning with Media Couple Card - Sulistyaningsih, Sri; Muharam, Agus; Rahman, Rahman; Sopandi, Wahyu; Sujana, Atep (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The aim of this study is to improve student activity and learning outcomes using the CTL model with the help of Couple Card media for IV grade students at SDN Rancaekek 05, Rancaekek District, Bandung Regency. This research is a Classroom Action Research (Classroom Action Research) model Kemmis and Mc. Taggart. The purpose of this study was to improve student activities and learning outcomes in social studies learning cultural diversity CLASS IV. The research was carried out in the first semester of the 2019/2020 academic year in two cycles. The subjects in this study were the IV grade students of SDN Rancaekek 05, totaling 39 students eith 20 male students and 19 female students. Data collection techniques used are tests and observations. Meanwhile, the data collection instrument used observation sheets and test questions. The results showed that there was an increase in student activity and learning outcomes in social studies learning class IV SDN Rancaekek 05. Student learning outcomes in the initial data, the average class was 68.2 for completeness there were 22 students (56.4%) and not yet completed there are 17 students (43.5%). This result does not meet the KKM, which is 75. In the first cycle, the increase in class average results is 71 for completeness there are 27 students (69.2%) and 12 students have not completed (30.7%) meaning there is an increase in the average score The average initial data to the first cycle is 2.8%, while the second cycle the results have increased again, namely the class average increased to 79.4 and completeness there are 32 students (82.1%) and 7 students have not completed ( 17.9%) thus, there is an average increase from cycle I to cycle II of 8.4%. In addition, the activeness of students in participating in learning has also increased. This is marked by the increased activeness of students in asking, answering questions and expressing opinions